THE RED-BLUE CHAIR (1918–1923) BY GERRIT RIETVELD: AN ANALYTICAL STUDY OF DE STIJL PRINCIPLES AND POST-WAR MODERNISM - Sharma, Manash Pratim; Toppo, Dimpoly (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Red-Blue Chair (1918–1923), designed by Gerrit Rietveld, is a seminal artifact of the De Stijl movement, embodying principles of geometric abstraction, minimalism, and functionalism. This study employs historical analysis and empirical examination to analyze the chair’s design, socio-political context, and influence on post-war Modernism, emphasizing its role in redefining furniture as a spiritual and artistic medium. Drawing on De Stijl ideologies, the chair’s orthogonal forms, primary colours, and mass-production potential reflect a response to World War I’s devastation, aiming to rebuild Europe through unified aesthetics. The analysis highlights Rietveld’s craftsmanship, colour application, and integration with architectural spaces such as the Schroder House. This study underscores the chair’s lasting impact on modern design, merging art, architecture, and societal ideals.